UPAYA HUKUM TERHADAP PENYALAHGUNAAN PERJANJIAN - Wiro Simbolon, Herbert Petrus; Dunia, Ngakan Ketut; Sukihana, Ida Ayu (Kertha Semaya : Journal Ilmu Hukum, 2013)
The right brand is a privilege as the privilege and the right to license the brand to a partyto use the trademark rights through licensing agreements. Lately there is a misuse oflicense both the licensor and the licensee to the detriment of either party and may result inunfair competition. Therefore, this article will explain about the legal effort to abuse thebrand license agreement
Keywords: The Right Brand, Trademark Licenses, Agreements, Unfair Competition